Cilostazol for Secondary Prevention of Stroke and Cognitive Decline: Systematic Review and Meta-Analysis. Issue 8 (August 2020) - McHutchison, Caroline; Blair, Gordon W.; Appleton, Jason P.; Chappell, Francesca M.; Doubal, Fergus; Bath, Philip M.; Wardlaw, Joanna M.
Abstract : Background and Purpose: Cilostazol, a phosphodiesterase 3' inhibitor, is used in Asia-Pacific countries for stroke prevention, but rarely used elsewhere. In addition to weak antiplatelet effects, it stabilizes endothelium, aids myelin repair and astrocyte-neuron energy transfer in laboratory models, effects that may be beneficial in preventing small vessel disease progression. Methods: A systematic review and meta-analysis of unconfounded randomized controlled trials of cilostazol to prevent stroke, cognitive decline, or radiological small vessel disease lesion progression. Two reviewers searched for papers (January 1, 2019 to July 16, 2019) and extracted data. We calculated Peto odds ratios (ORs) and 95% CIs for recurrent ischemic, hemorrhagic stroke, death, adverse symptoms, with sensitivity analyses. The review is registered (CRD42018084742). Results: We included 20 randomized controlled trials (n=10 505), 18 in ischemic stroke (total n=10 449) and 2 in cognitive impairment (n=56); most were performed in Asia-Pacific countries. Cilostazol decreased recurrent ischemic stroke (17 trials, n=10 225, OR=0.68 [95% CI, 0.57–0.81]; P <0.0001), hemorrhagic stroke (16 trials, n=9736, OR=0.43 [95% CI, 0.29–0.64]; P =0.0001), deaths (OR=0.64 [95% CI, 0.49–0.83], P <0.0009), systemic bleeding (n=8387, OR=0.73 [95% CI, 0.54–0.99]; P =0.04), but increased headache and palpitations, compared with placebo, aspirin, or clopidogrel. Cilostazol reduced recurrent ischemic stroke more when given long (>6 months) versus short term without increasing hemorrhage, and in trials with larger proportions (>40%) of lacunar stroke. Data were insufficient to assess effects on cognition, imaging, functional outcomes, or tolerance. Conclusions: Cilostazol appears effective for long-term secondary stroke prevention without increasing hemorrhage risk. However, most trials related to Asia-Pacific patients and more trials in Western countries should assess its effects on cognitive decline, functional outcome, and tolerance, particularly in lacunar stroke and other presentations of small vessel disease. Abstract : Supplemental Digital Content is available in the text.